International recommendations for an effective control of head louse infestations. (7th August 2020) - Mumcuoglu, Kosta Y.; Pollack, Richard J.; Reed, David L.; Barker, Stephen C.; Gordon, Shirley; Toloza, Ariel C.; Picollo, Maria I.; Taylan‐Ozkan, Aysegul; Chosidow, Olivier; Habedank, Birgit; Ibarra, Joanna; Meinking, Terri L.; et al.
Abstract: Head louse infestations continue to be a concern of public health in most countries, including the most developed ones. The present recommendations are intended to inform and stress the role and impact of the different authorities, institutions, industry, and the public in the control of head lice in order to reduce the prevalence of this parasite. We encourage health authorities to pursue more effective methods to correctly identify such infestations, and evaluate existing and new pediculicides, medical devices, louse repellents, and louse‐ and nit‐removal remedies. Pediculicides and medical devices must have verifiable claims in the instructions for use and should be tested periodically to document current levels of resistance by lice to the active ingredients and to the formulated products. Where the prevalence of lice is claimed to be epidemic, children should be periodically evaluated objectively to document the actual level of prevalence. Continuing education for health providers and the general population promises to correct misinformation regarding the biology, prevention, and management of lice. Parents should regularly inspect their children for head lice and treat as necessary. Health authorities are encouraged to eliminate policies and practices that rely upon school exclusion as a means to reduce incidence and prevalence, e.g., the 'no‐nit' policy which lacks scientific justification, and are counterproductive to the health and welfare of children.